Studi In Silico Senyawa Aktif Minyak Ikan Tindarung Sebagai Penurun Kolesterol Melalui Inhibitor HMG-KoA - RUMALUTUR, CHRISTHALIA IEWANDA; PANI, PUTRI MARGARETHA GLAUDY; PRAYOGA, DESHANDA KURNIAWAN; LAPIAN, ALDA JULISTY GABRIELA; GONI, BRIGITA CHRISTANIA AURORA; FATIMAWALI; ANTASIONASTI, IRMA (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2024)
Tindarung fish oil contains omega-3 fatty acids, namely DHA (Docosahexaenoic acid) and EPA (Eicosapentaenoic acid). Therefore, tindarung fish oil has the potential to be developed as a cholesterol drug. This study aims to determine the activity of HMG-CoA reductase from fatty acids of tindarung fish oil using an in silico study with molecular docking. The receptor used was the enzyme HMG-CoA reductase (PDB ID: 1HW9) with the native ligand simvastatin prepared using YASARA. The fatty acid compounds were drawn using MarvinSketch at pH 7.4 with 10 confirmations. In the molecular anchoring process, the PLANTS program was used and visualized in 2D with Discovery Studio Visualizer and in 3D with Pymol. The native ligand showed a docking value of -76.4052. Compounds 1,2,3,8,11, and 12 had relative values for simvastatin of more than 95%. These compounds have molecular anchoring activity similar to simvastatin so it is predicted to be able to reduce cholesterol levels by inhibiting the HMG-CoA reductase enzyme.